Does electric field nonuniformity affect gas breakdown? - Lisovskiy, V.A.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2015)
This paper presents the results of studying the gas breakdown in the nonuniform constant electric field. We registered the discharge breakdown curves in nitrogen between flat electrodes of 12 mm in diameter and spaced 5 and 25 mm apart whereas the chamber diameter was 56 mm. We demonstrate that in contrast to previous studies with the narrow gap between the electrodes and the chamber wall the breakdown curves for different space values actually coincide when plotted to the U(pL) scale. The Paschen law holds under conditions of our experiments though the inter-electrode spacing exceeds almost fourfold the electrode radius and the electric field axial profile for a larger spacing possesses a minimum at the inter-electrode gap center. Consequently, under condition studied the electric field nonuniformity did not affect practically the breakdown process.